Dandelion (Taraxacum officinale) - Hepatoprotective Herb with Therapeutic Potential - Singh, Amritpal; Malhotra, Samir; Subban, Ravi (Pharmacognosy Reviews)
Extracts of the dried leaves of dandelion (Taraxacum officinale G.H. Weber ex Wiggers. (Asteraceae) are used in traditional medicine for gastrointestinal and hepatic diseases. The plant is valued as laxative and diuretic. Lately, several research and review papers have highlighted hepatoprotective property of specific herbals like Kalmegh (Andrographis paniculata Nees.) and Kutki (Picrorhiza kurroa Benth.) from Traditional Indian Medicine (TIM) and milk thistle (Silybum marianum L.) from Western Botanical Medicine. Market studies show dandelion to be ingredient of liver and gall bladder preparations. Little data is available on pre-clinical and clinical studies done on the plant. Since concept of reverse pharmacology is rapidly catching up for discovering ‘leads’ from plants, it is worthwhile to conduct scientific studies on dandelion to support the traditional use. The studies may provide evidence in support of additional indications, both traditional and novel.
Keywords: Hepatoprotective-Cholagouge- Dandelion- Taraxacum officinale